Factors Affecting Implementation Practice Dental Nurse Sterilization Equipment In Dentistry - Sadimin Sadimin; Sariyem Sariyem; Irmanita Wiradona (Jurnal Riset Kesehatan, 2014)
The purpose of this study was to analyze the factors that affect the practice of sterilization of dental instruments to prevent cross infection in Semarang Health Center. This is a quantitative research done with survey method and cross sectional study. The population and the sample were 37 dental nurses who work in the Semarang Health Center. Whereas, the data were collected by using a structured questionnaire. Result shows that 54.1 % of the respondents in both practice sterilization. The first influencing variable is knowledge of the dental nurses ( p = 0.014 ) with 10,529 points odds ratio, which means that dental nurses with good knowledge of sterilization have possibility to execute the patients 10 times better than those with less good knowledge. The second is the attitude of dental nurses (p = 0.037) with 7.104 points odds ratio, which means that dental nurses with good attitude have the possibility to sterilize 7 times better than those who show a less good attitude. Variables that do not affect the practice of sterilization is the level of education, availability of sterilization, age, gender, years of service, rules relating to sterilization.